A cDNA Immunization Strategy to Generate Nanobodies against Membrane Proteins in Native Conformation - Eden, Thomas; Menzel, Stephan; Wesolowski, Janusz; Bergmann, Philine; Nissen, Marion; Dubberke, Gudrun; Seyfried, Fabienne; Albrecht, Birte; Haag, Friedrich; Koch-Nolte, Friedrich (Frontiers in Immunology, 2018)
Nanobodies are soluble, versatile, single-domain binding modules derived from the VHH variable domain of heavy chain antibodies naturally occurring in camelids. Nanobodies hold huge promise as novel therapeutic biologics. Membrane proteins are among the most interesting targets for therapeutic nanobodies because they are accessible to systemically injected biologics. In order to be effective, therapeutic nanobodies must recognize their target membrane protein in native conformation. However, raising nanobodies against membrane proteins in native conformation can pose a formidable challenge since membrane proteins typically contain one or more hydrophobic transmembrane regions and therefore are difficult to purify in native conformation. Here we describe a highly efficient genetic immunization strategy that circumvents these difficulties by driving expression of the target membrane protein in native conformation by cells of the immunized camelid. The strategy encompasses ballistic transfection of skin cells with cDNA expression plasmids encoding one or more orthologs of the membrane protein of interest and, optionally, other co-stimulatory proteins. The plasmid is coated onto 1 µm gold particles which are then injected into the shaved and depilated skin of the camelid. A gene gun delivers a helium pulse that accelerates the DNA coated particles to a velocity sufficient to penetrate through multiple layers of cells in the skin. This results in the exposure of the extracellular domains of the membrane protein on the cell surface of transfected cells. Repeated immunization drives somatic hypermutation and affinity maturation of target-specific heavy chain antibodies. The VHH/nanobody coding region is PCR-amplified from B cells obtained from peripheral blood or a lymph node biopsy. Specific nanobodies are selected by phage display or by screening of nanobody-based heavy chain antibodies expressed as secretory proteins in transfected HEK cells. Using this strategy, we have successfully generated agonistic and antagonistic nanobodies against several cell surface ecto-enzymes and ligand-gated ion channels.